The absence of presence: homiletical reflections on Luther's notion of the masks of God (larvae dei) - J. Cilliers (Acta Theologica)
This paper addresses a complex but core issue of preaching, namely the experience of the elusiveness of God’s presence (revelation) by taking cognisance of the notion of masking. Besides being a common cultural phenomenon, the art of masking could also be evaluated theologically and therefore homiletically. Luther’s understanding of the masks of God (larvae dei) is introduced into the discussion, and a number of homiletical implications are drawn in view of the continuous tension that exists between God’s revealing and his concealing.